Manajemen Pendidikan Islam Perspektif Al-Qur’an dan Hadist - M. Fikri Haikal (Journal on Education, 2023)
Al-Qur'anul Karim, the Muslim holy book, for example, is described as a "hudan" which is loaded with various guidelines to be a good caliph on earth. In order to truly utilize the content of the Qur'an in relation to complex situations that have arisen, occurred, or have not yet occurred, Muslims must study the Qur'an themselves to follow these recommendations. The Qur'an answers all questions about the existence of nature and human life. The Qur'an makes this claim, discussing everything from the causes of human events to human actions, in this case educational leadership